Systematic Literatur Review: Identifikasi Keefektifan Pembelajaran Daring di Indonesia: (Systematic Literature Review: Identification Effectiveness of Online Learning in Indonesia) - Dayana Fazira; Ayu Fitri Jumain; Vira Putri Fadhilah; Putri Puspita Sari; Miftha Sandia Arilla; Erna Suyanti (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2023)
Online learning (e-learning) is a learning system that is used to provide educational materials to students by accessing the internet through platforms. The purpose of this research is to obtain information about the effectiveness of the online learning process in Indonesia. The study used a systematic literature review (SLR) method. With the stages of identifying, reviewing, evaluating, and interpreting all available research. The results of this study are that online learning is less effective due to the lack of facilities and infrastructure and the unpreparedness of technology education. The lack of facilities and infrastructure that is influenced by economic factors and technological unpreparedness is also an obstacle in the ongoing online learning activities. So that the learning outcomes provided by students are not 100% smooth or effective. Key words: online learning, learning effectiveness, Covid-19 pandemic. Â ABSTRAK Pembelajaran daring (e-learning) adalah sistem pembelajaran yang digunakan untuk memberikan materi pendidikan kepada siswa dengan mengakses internet melalui platform. Tujuan penelitian ini adalah mendapatkan informasi tentang keefktifitasan proses pembelajaran daring di Indonesia. Penelitian menggunakan metode sistematika literature review (SLR). Dengan tahapanÂ mengidentifikasi, meninjau, mengevaluasi, dab menafsirkan semua penelitian yang tersedia. Hasil dari penelitian ini adalah kurang efektif nya pembelajaran daring karena faktor kurangnya sarana dan prasarana serta ketidaksiapan edukasi teknologi. Kurang nya sarana dan prasarana yang dipengaruhi oleh faktor ekonomi dan ketidaksiapan teknologi juga menjadi suatu hambatan dalam berlangsungnya kegiatan belajar online. Sehingga hasil belajar yang diberikan oleh pemelajar tidak 100% lancar atau efektif. Â Kata kunci: pembelajaran daring, efektifitas belajar, pandemi Covid-19.